Effect of Voltage on Radiation Characteristics of Triggered Vacuum Diode - Wei Tian; Shixiu Chen; Jixiong Xiao; Kun Chen; Fei Gai (Institute of Advanced Engineering and Science, 2013)
Based on the conduction mechanism of vacuum trigger diode, an experimental scheme has been designed to research on the effect of voltage parameters on radiation characteristics of vacuum trigger diode. The factors affecting radiation characteristics of vacuum trigger diode were analyzed. With increase of charging voltage, the trigger current increases, the radiation enhances and radiation band moves up. With increase of anode-cathode voltage, more high density plasma of anode is generated by the electron bombardment anode, the radiation enhances and upper frequency limit is expanded. So the theoretical analysis is proved. Because of trigger electrode, the vacuum diode can be controlled more flexibly and conveniently. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3746